Celiac Disease as a Rare Cause of Membranous Nephropathy: A Case Report - Pestana, Nicole; Vida, Carlota; Durães, José; Silva, Gil; Vieira, Pedro (My University, 2021)
Membranous nephropathy is the most common cause of nephrotic syndrome in adults. A non-negligible number of cases are associated with systemic conditions. We report a case of a 50-year-old man who presented with nephrotic syndrome six months after being diagnosed with celiac disease. Although the patient showed disappearance of circulating immunoglobulin A (IgA) anti-tissue transglutaminase antibodies following a gluten-free diet, he had a sudden onset of nephrotic syndrome presenting with severe hypoalbuminemia. Other secondary causes were promptly excluded leading to the assumption of celiac disease-associated membranous nephropathy with remission after treatment with angiotensin system blockade and a gluten-free diet. The goal of this case report is to alert the clinic towards this rare association aiming for an early diagnosis and adequate selection of long-term therapy.
Keywords: membranous nephropathy; celiac disease; nephrotic syndrome; Madeira Island; Portugal; sindrome nefrótico